Localização gravitacional de modelos em seis dimensões com brana espessa tipo-corda - Brandão, Waldo Hosternes Peixoto (2019)
One of the premises of the present research is to smooth the Guergueta-Shaponishkov (GS) model as an approximate special case. The following are some conditions physically accepted obeyed in all the solutions described in this abstract, such as: those of regularity for a thick string-like braneworld as well as that of energy. Specific analytical solutions of the Einstein Equation that smooth the GS model were analyzed, except for an exotic brane model. In addition, two analytical solutions, that smooth the GS model of the Einstein equation of general nature are considered to have the same pressure scalars, which may require the calculation of a well defined integral by numerical integration, if needed. Such scalars can be of energy, as associated physically if they are equal. It was also developped in such context, a differential solution of the general kind, which can smooth the GS model by the determined conditions as followed in special case. Then, in the special case from this differential solution, coherently was developed one of the related general analytical solutions. It was also developed an approximative solution method for the whole domain of the solution that smoothes the GS model and for the Einstein Equation, as well as the gravity localization, that is expected to be of exact convergence due to the established conditions which allow that the equal pressure scalars be chosen. It is so studied the localization of gravitational perturbations, describing, in a consistent manner, the analogous potential of Schröedinger and the Hierarchy Problem. Thus, it was possible to associate the Newtonian potential for short distances following the 4D Yukawa Potential, through a static thick string-like braneworld associated to 2D bulk space with cylindrical symmetry.